The Pengembangan Media Pembelajaran Fisika Menggunakan Gutasi (Game Ular Tangga Fisika) - Falensia, Maria (Universitas Tadulako, 2023)
This study aims to determine the feasibility of gutasi media in physics learning, to determine student responses in learning using guttation media, and to determine the increase in student learning outcomes when using guttation media. This type of research is a development using the ADDIE model. The subjects of this study were grade VIII students of SMP Negeri 14 Sigi for the 2020/2021 academic year. The results of the questionnaire analysis showed that the average score for the material expert assessment was 3.41 and was categorized as